2020
DOI: 10.1038/s41598-020-66558-w
|View full text |Cite
|
Sign up to set email alerts
|

Associations among neurophysiology measures in irritable bowel syndrome (IBS) and their relevance for IBS symptoms

Abstract: Abnormal gut-brain interactions are common in irritable bowel syndrome (iBS), but the associations between neurophysiological measures and their relation to gastrointestinal (Gi) symptoms are poorly understood. Our aim was to explore these relationships and define the most relevant neurophysiology measures for Gi symptom severity in iBS. iBS patients underwent small intestinal motility (manometry; fasted and fed contraction frequency, phase III time) and secretion (transmural potential difference), rectal sens… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 54 publications
(68 reference statements)
0
8
0
Order By: Relevance
“…Overall, gut microbes in IBS-D demonstrate a profile consistent with increased utilization of multiple energy sources. It is unclear if these metabolic shifts promote symptoms in IBS-D or reflect adaptation of gut microbes to altered GI motility and secretion in IBS-D [ 71 ]. Of note, metabolites reported in other studies to differentiate IBS bowel habit subtypes such as tryptamine were not differentially abundant in this study, potentially reflecting the previously noted differences in study population and analytic strategy [ 14 ].…”
Section: Discussionmentioning
confidence: 99%
“…Overall, gut microbes in IBS-D demonstrate a profile consistent with increased utilization of multiple energy sources. It is unclear if these metabolic shifts promote symptoms in IBS-D or reflect adaptation of gut microbes to altered GI motility and secretion in IBS-D [ 71 ]. Of note, metabolites reported in other studies to differentiate IBS bowel habit subtypes such as tryptamine were not differentially abundant in this study, potentially reflecting the previously noted differences in study population and analytic strategy [ 14 ].…”
Section: Discussionmentioning
confidence: 99%
“…However, the use of CTT is limited when differentiating between different forms of GI disorders and provides limited information relating to the pathophysiology of GI dysmotility. 26 Moreover, it is important to acknowledge that GI symptoms, such as constipation, diarrhoea and bloating are not always associated with gut dysmotility, 27 suggesting that the GI symptoms experienced by patients in this study may not be specific to the lower GI tract or to GI dysmotility. A number of patients had persistent loose stool throughout the study.…”
Section: Discussionmentioning
confidence: 91%
“…Interestingly, clinical studies have shown that increased compliance is associated with increased sensation in healthy volunteers [49,50]. However, whether this relationship extends to non-physiological conditions such as IBD [51] or IBS [52,53] still has to be studied in more detail. The mechanism underlying the observed alterations in colonic compliance requires further investigation.…”
Section: Discussionmentioning
confidence: 99%